Public Speaking Aversion - Buser, Thomas; Yuan, Huaiping (Management Science, 2023)
Fear of public speaking is very common, but we know little about its implications for individuals and organizations. We establish public speaking aversion as an economically relevant preference using three steps. First, we use laboratory and classroom experiments to show that preferences for speaking in public vary strongly across individuals with many participants willing to give up significant amounts of money to avoid giving a short presentation in front of an audience. Second, we introduce two self-reported items to elicit preferences for speaking in public through surveys. We show that these items are strongly related to choices in the incentivized laboratory experiment and that public speaking aversion is distinct from established traits and preferences, including extraversion. Third, we elicit these items in a survey of business and economics students and show that public speaking aversion predicts career expectations. Public speaking–averse individuals avoid careers in management consulting and are more attracted to data analyst and back office careers. This paper was accepted by Axel Ockenfels, behavioral economics and decision analysis. Funding: This project has received funding from the European Research Council under the European Union’s Horizon 2020 research and innovation program [Grant 850590]. Supplemental Material: The online appendix and data are available at https://doi.org/10.1287/mnsc.2022.4500 .